From Tawhid to Exemplary Practice: Islamic Values in the Parenting Practices of Muslim Families - Widia, Arneta; Safitri, Inayatu; Siregar, Zuhrona; Sitorus, Masganti (EDUCTUM: Journal Research, 2025)
This study aims to describe and analyze Islamic values ??embodied in parenting practices and their application in the lives of modern Muslim families. Using a qualitative descriptive approach through library research, this study examined various academic sources such as journals, books, and scientific articles published between 2015 and 2025. The results show that Islamic parenting is based on the values ??of monotheism, compassion (rahmah), responsibility (amanah), discipline, honesty, and role models (uswah hasanah). These values ??are the main foundation in shaping the character of children who are faithful, have noble morals, and are competitive in the global era. The implementation of Islamic parenting is not only through verbal teaching, but also through habituation, role models, and compassionate communication. In the digital era, challenges such as the influence of technology and differences in values ??between generations require parents to integrate Islamic principles with modern parenting approaches. Thus, Islamic values ??remain relevant and can serve as effective guidelines in forming harmonious families and a generation of Muslims who are noble and adaptive to current developments.